Jurnal Kata: a critical comparative reading of nationalism in pramoedya a. toer and ngugi wa thiong'o - Sunardi, D. (Prodi Bahasa Inggris Fak sastra PETRA, 2015)
this article tries to explore how the conception, birth, and development of novel can become a tool to shed lights to our understanding of the conception, birth, and development of nationalism